2016
DOI: 10.1007/s00402-016-2511-z
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of endoscopy for recalcitrant greater trochanteric pain syndrome

Abstract: While the majority of patients with GTPS will improve with non-operative management, endoscopic iliotibial band release, trochanteric bursectomy and gluteal tendon repair is a safe and effective treatment for severe recalcitrant cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Our results show that postoperative satisfaction, pain scores and OHS were significantly worse in cases with previous THA compared to idiopathic cases. With these patients making up 40% of cases in our series, our data add to those presented by Baker et al [14], and are of significance because a consistent and major exclusion factor in studies of outcome following surgery for GTPS is previous ipsilateral THA [13,15].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results show that postoperative satisfaction, pain scores and OHS were significantly worse in cases with previous THA compared to idiopathic cases. With these patients making up 40% of cases in our series, our data add to those presented by Baker et al [14], and are of significance because a consistent and major exclusion factor in studies of outcome following surgery for GTPS is previous ipsilateral THA [13,15].…”
Section: Discussionsupporting
confidence: 79%
“…Many studies looking at the efficacy of surgical techniques for GTPS exclude patients who have undergone previous THA [15,13]. However, these patients may make up a significant proportion of refractory cases:…”
Section: Introductionmentioning
confidence: 99%
“…Fox 14 found good or excellent results in 23 of 27 patients undergoing bursectomy with no reported intervention to the iliotibial band. Drummond et al 9 reported improvement on both the Oxford Hip Score and International Hip Outcome Tool (iHOT-33) 20 months after surgery in a retrospective analysis of 49 patients undergoing arthroscopic ITBR and bursectomy, although they included 7 cases that presented full-thickness tendon tears and were repaired, making the comparison between results more complex. Baker et al, 1 in a prospective cohort study of 25 patients, reported an improvement of 26 points on the mHHS at 22 months.…”
Section: Discussionmentioning
confidence: 99%
“…8 These patients report persistent pain in the lateral hip and may demonstrate weak or painful hip abduction. 10,14,19 Full- and partial-thickness tears of the gluteus medius are increasingly being reported as an underdiagnosed cause of this recalcitrant hip pain. 10,13,14,19 If left untreated, these tears can progressively worsen, cause chronic hip pain and weakness, and affect the gait of the patient.…”
mentioning
confidence: 99%
“…10,14,19 Full- and partial-thickness tears of the gluteus medius are increasingly being reported as an underdiagnosed cause of this recalcitrant hip pain. 10,13,14,19 If left untreated, these tears can progressively worsen, cause chronic hip pain and weakness, and affect the gait of the patient. 9 Patients with gluteus medius tears and 6 months of unsuccessful conservative therapy may be considered candidates for surgical repair.…”
mentioning
confidence: 99%